TANTANGAN PROGRAM SEKOLAH PENGGERAK DALAM PERSPEKTIF STREET-LEVEL BUREAUCRACY DAN BIROKRASI IDEAL - Edrico Arya Utama; Shakhila Dwi Suryani; Agung Faizs Syaputra; Septina (Educational Research Center, 2025)
The School Mover Kegiatan represents a significant policy initiative aimed at enhancing the quality of national education by bolstering student competencies, refining the functions of teachers and principals, and leveraging educational technology. This research seeks to examine the dynamics involved in the implementation of the School Mover Kegiatan through a descriptive qualitative lens, particularly informed by Max Weber's concept of ideal bureaucracy and Michael Lipsky's theory of street-level bureaucracy. Data for this study were gathered through desk research and document analysis, encompassing a variety of research outcomes, official regulations, and pertinent academic literature. The findings of the study reveal that while the School Mover Kegiatan has established a systematic intervention framework that incorporates consultative and asymmetric mentoring, enhancement of school human resources, a new paradigm for learning, data-driven planning, and the digitalization of schools, its execution continues to encounter numerous structural and cultural obstacles. These obstacles include insufficient competencies among teachers and principals, excessive administrative burdens, inequalities in digital infrastructure, teacher rotation issues, budget constraints, and resistance to change. Furthermore, the analysis indicates that the effectiveness of the kegiatan is significantly shaped by the actions of policy implementers at the school level, who possess considerable discretion in how they interpret and apply policies. The disparity between the rational-formal tenets of ideal bureaucracy and the adaptability of street-level bureaucracy emerges as a critical factor influencing the successful execution of this policy. Therefore, strengthening the capacity of implementers, policy consistency, and collaboration among stakeholders are necessary to ensure the School Mover Kegiatan is effective, sustainable, and capable of realizing equitable educational transformation.